Symbolic Meaning Movements Dewi Tri Sekti Dance: A Study Of Denotative And Conotative Semiotics - Azizah, Nurul; Indah Pebrianti, Sestri; Indriyanto , Indriyanto (Jurnal Seni Tari, 2025)
This study aims to examine the symbolic meaning of movement in Dewi Tri Sekti Dance created and performed at the Sekar Kinasih Studio, Kuwasen Village, Jepara Regency. The main focus of the study is to reveal the symbolic meaning of movement, which is studied through the denotative and connotative meanings contained in the dance movements through Roland Barthes' semiology approach. The method used is descriptive qualitative with data collection techniques in the form of direct observation of the creative process and dance forms, in-depth interviews with key informants (choreographers and dancers), and visual documentation. Data analysis is carried out through the stages of data reduction, data presentation, and inductive conclusion drawing. Data validity through triangulation of sources, methods, and theories. The results of the study show that the denotative meaning as textual is contained in the movement structure of the Dewi Tri Sekti Dance, with the beginning, the core, and the end. The dance movements not only function as aesthetic elements, but also have a contextual meaning that represents cultural values, local historical narratives, and women's identities in Jepara society.